Role of the plasma membrane proton pump in pH regulation in non-animal cells. - Sanders, D (1981)
Possible methods by which eukaryotic cells can regulate intracellular pH (pHi) in response to experimental acid loading were investigated by using as a model cell the fungus Neurospora. Attention was focused on the role of membrane transport in such regulation, starting from the fact that this organism possesses a powerful electrogenic proton extrusion pump. Intracellular acidification was forced by introducing butyric acid into the recording medium, and subsequent changes in pHi and membrane potential were determined with intracellular microelectrodes. In separate experiments, membrane current-voltage curves were obtained and resolved--by an explicit kinetic model--into distinct pump and leak components. Decreased pHi causes increased outward pumping of H+ ions, in a manner quantitatively consistent with their role as a substrate for the proton pump. This increased pumping is often manifest as a transient hyperpolarization at the onset of cytoplasmic acidification. With a considerably slower time course, decreased pHi also produces a large increase in membrane leak conductance, which brings about net membrane depolarization and further stimulates the pump (by virtue of the reduced back electromotive force). Although the identity of the ion responsible for increased leak conductance is not yet known, the evident modulation of conductance seemingly plays an important role in stabilizing the intracellular pH: Stimulation of the pump alone would have little net effect on pHi because it would result simply in enhanced backflux of H+ (to which the membrane is most permeable in normal circumstances). An increased leak to nonprotons, however, would allow the pump to accomplish net H+ ejection.